Forest logging and it impact on soil carbon dioxide effluxin the tropical forest, Peninsular Malaysia - Mande, Hosea Kato; Abdullah, Ahmad Makmom; Aris, Ahmad Zaharin; Nuruddin, Ahmad Ainuddin; Binyemed, Fadel Mohamed; Ben Youssef, Khaleed Ali Ahmed (International Organization of Scientific Research, 2014)
Forest harvesting is expected to have an impact on soil CO2 efflux as it influence soil properties and changes in microclimatic conditions which can have implications on the regional carbon balance. Soil CO2 efflux was measured using a continuous open flow chambers technique connected to a multi-gas-handling unit and infrared CO2/H2O gas analyser. Soil temperature, soil moisture, water potential, Total Organic Carbon (TOC), Soil Organic Carbon (SOC), Soil Organic Carbon stock (SOCstock), Bulk density and pH were examinedto ascertain their contribution onsoil CO2 efflux and effect ofenvironmental factors in a canopy gap created through the logging of groups of trees in the Sungai Menyala forest, Peninsular Malaysia.